WHAT DOESN'T KILL ME MAKES ME STRONGER ARE THE ADVERSE LIFE EVENTS THE PREREQUISITE FOR MATURATION AND GROWTH? - Aslam, Naeem (Journal of Ayub Medical College Abbottabad, 2012)
The relationship between adversity and growth is well documented.1 Religion, philosophy and literature is full of the examples that showed that some level of adversity is necessary for maturation and growth. This is also the central theme of the humanistic and existential movements of psychology that a confrontation with tragedy is often precursors to self-actualisation. Viktor Frankl wrote about the will to meaning following his experiences in Theresienstadt and Auschwitz are common examples of this idea.2 Nietzsche's famous dictum, What doesn't kill me makes me stronger is the same expression of this idea. It is not the event itself but the subjective cognitive appraisal and struggle to the adversity is related to growth.1 Researchers have used a number of different terms to describe individuals' reports of positive outcomes in the face of adversity, including posttraumatic growth, adversarial growth, benefit-finding, stress-related growth, perceived benefits and thriving etc.3 Each term refers to a slightly different phenomenon. Several models have been proposed regarding the occurrence of Posttraumatic Growth. These include the Functional Descriptive Model4, Organismic Valuing Theory5 and Biopsychosocial-Evolutionary Theory. Although with some variation, these models hypothesise that the experience of a highly stressful or traumatic event shatters an individual's basic beliefs about the self and the world. In terms of that the persons perceives the changes in relationship with others, personal life philosophy and spiritual changes.4 Growth or positive outcomes have been reported following a variety of traumatic experiences, including motor vehicle accidents6, terrorist attacks7, leukaemia8, and cardiac disease9, etc. Findings showed that growth is not equal in all sorts of adversities. It depends upon the nature and intensity of the adversity. Moreover, the patterns are growth is different across gender and age. For example studies showed that female exhibit more posttraumatic growth as compare to male,3 and age is positively associated with stress symptoms and negatively with Posttraumatic Growth (PTG)10. Question arises how much adversity is sufficient for growth. Studies showed that very low level of trauma or high level of trauma may is not associated with growth. However, a moderate level of trauma is associated with the growth. Mostly a curvilinear relation has been found between PTG and adversity, i.e., a moderate level of adversity is associated with positive growth.11,12 The focus of the most of the past researches was to uncover the adverse consequences of the traumatic accidents. Hence, the association of psychopathology and adversity is well studied. There is scarcity of research on this aspect of relationship between the adversity and growth. This editorial is aimed to raise interest to conduct the studies that find the predictive role of daily life stressor to positive changes and maturity. Adversities are the integral part of life and cannot be avoided. Despite constant avoidance, we have to face adversities. These cannot be eliminated but can be managed with proper adversity management trainings. Adversities are the best mentors. Although we strive to avoid adversities and protect the children from bad events. Over protective parenting may hinder the growth and maturity of the offspring's by buffering and providing shields them from the real life challenges and problems of life. Parents should give the children space to resolve daily life difficulties and challenges. It will help to lead them to the deliberate ruminations, increase their confidence, self efficacy, problem solving abilities and decision making skills. On this children might develop the sense that they have to '˜live with problems' and '˜problem-free life' does not exist. Instead of dwelling on the problems they have to deal it. As a result they come out of adversity with new strengths and with better coping skills. As most of the current social scientists suggest that some shocking experience is necessary for a child to be a realistic person.